Quantitative Visions of Reality at the Tick-Host Interface: Biochemistry, Genomics, Proteomics, and Transcriptomics as Measures of Complete Inventories of the Tick Sialoverse - Mans, Ben J. (Frontiers in Cellular and Infection Microbiology, 2020)
Species have definitive genomes. Even so, the transcriptional and translational products of the genome are dynamic and subject to change over time. This is especially true for the proteins secreted by ticks at the tick-host feeding interface that represent a complex system known as the sialoverse. The sialoverse represent all of the proteins derived from tick salivary glands for all tick species that may be involved in tick-host interaction and the modulation of the host's defense mechanisms. The current study contemplates the advances made over time to understand and describe the complexity present in the sialoverse. Technological advances at given periods in time allowed detection of functions, genes, and proteins enabling a deeper insight into the complexity of the sialoverse and a concomitant expansion in complexity with as yet, no end in sight. The importance of systematic classification of the sialoverse is highlighted with the realization that our coverage of transcriptome and proteome space remains incomplete, but that complete descriptions may be possible in the future. Even so, analysis and integration of the sialoverse into a comprehensive understanding of tick-host interactions may require further technological advances given the high level of expected complexity that remains to be uncovered.